Kinetics of PbCrO(4) nanorod growth by oriented attachment at the air-water interface - Hawaldar, Ranjit R.; Sathaye, Shivaram D.; Harle, Arti S.; Gholap, Ramkrishna S.; Patil, Kashinath R. (Journal of Physical Chemistry C, 2008)
Oriented attachment is a new way of crystal growth to transform preformed nanoparticles into hierarchical assemblies. Here, we demonstrate the use of liquid-liquid interfaces toward the formation of PbCrO(4) nanoparticles and their subsequent time-dependent self-assembly at the air-water interface into nanorods by oriented attachment. EDAX and XPS analysis indicate the formation of stoichiometric PbCrO(4). TEM studies at different stages of aging reveal that the transformation from nanoparticles to nanorods is kinetically governed. HRTEM analysis indicates nanorod growth along the [110] plane. UV-visible spectra reveal the presence of peaks at 425 and 515 nm for nanorods, while for the nanoparticle sample, a single peak at 425 urn is evident. As formation of ultrathin films over a large area (typically equal to or greater than 1 mu m x 1 mu m) concomitantly accompanies this approach, it can be extended to other materials as well for nanostructured device applications.

Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.

Facile room temperature synthesis of ZnO nanoflower thin films grown at a solid-liquid interface - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Materials Science, 2014)
Hierarchical ZnO films consisting of nanoflower particulates are successfully grown by a solid-liquid interface reaction technique at room temperature without additives like surfactants, capping agent, or complexing agent. The structural, morphological, and photocatalytic properties of these films are studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-Vis spectroscopy. The nucleation, growth processes and hence the resulting morphology of the end product can be regulated by changing the concentration of LiOH and the time of reaction. SEM throws light on the chronology of the flower formation by studying the intermediate morphology. Electron microscopy results indicated that these ZnO nanostructures self-assembled to produce flower-like nanostructures. The highest photocatalytic efficiency was observed for the films prepared at the concentration of LiOH 0.5 mg/mL in ethanol at 24 h. On the basis of the results, a plausible growth mechanism for the formation of flower-like ZnO nanostructures is discussed.

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Architecturally designed Pt-MoS2 and Pt-graphene composites for electrocatalytic methanol oxidation - Patit, Sagar H.; Anothumakkool, Bihag; Sathaye, Shivaram D.; Patil, Kashinath R. (Physical Chemistry Chemical Physics, 2015)
Thin films consisting of platinum nanoparticles (Pt NPs) with uniform size and distribution have been successfully prepared at a liquid-liquid interface. Apart from the usual substrates like glass, Si etc. the films were also deposited on the surfaces of MoS2 thin films and graphene nanosheets (GNS) respectively, by using a layer-by-layer (LbL) deposition technique to form Pt-MoS2 and Pt-GNS composites. The loading concentration of Pt NPs on MoS2 and GNS can be adjusted by selecting the number and sequence of the component layers during LbL deposition. The Pt thin films, Pt-MoS2 and Pt-GNS nanocomposite thin films are characterized using transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray spectrometry (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). TEM results of the composites show that Pt NPs with sizes in the range of 1 to 3 nm are uniformly dispersed on the MoS2/GNS surface. The catalytic activities of Pt and Pt-composites for the reaction of methanol oxidation are studied using cyclic voltammetry and chronoamperometry. Electrochemical studies reveal that both the Pt-MoS2 and Pt-GNS nanocomposites show excellent electrocatalytic activity towards methanol oxidation. Pt-MoS2 and Pt-GNS nanocomposite electrodes show excellent stability for reuse of the catalyst. A probable mechanism of catalysis has been discussed. We propose that the similar architecture reported here would be promising for the synthesis of high performance catalysts for fuel cells, gas phase reactions, and other applications such as sensors.

Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3

Situ preparation of N-TiO2/graphene nanocomposite and its enhanced photocatalytic hydrogen production by H2S splitting under solar light - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Ambekar, Jalindar D.; Park, Chan-J.; Kale, Bharat B. (Nanoscale, 2015)
Highly monodispersed nitrogen doped TiO2 nanoparticles were successfully deposited on graphene (N-TiO2/Gr) by a facile in-situ wet chemical method for the first time. N-TiO2/Gr has been further used for photocatalytic hydrogen production using a naturally occurring abundant source of energy i.e. solar light. The N-TiO2/Gr nanocomposite composition was optimized by varying the concentrations of dopant nitrogen and graphene (using various concentrations of graphene) for utmost hydrogen production. The structural, optical and morphological aspects of nanocomposites were studied using XRD, UV-DRS, Raman, XPS, FESEM, and TEM. The structural study of the nanocomposite shows existence of anatase N-TiO2. Further, the details of the components present in the composition were confirmed with Raman and XPS. The morphological study shows that very tiny, 7-10 nm sized, N-TiO2 nanoparticles are deposited on the graphene sheet. The optical study reveals a drastic change in absorption edge and consequent total absorption due to nitrogen doping and presence of graphene. Considering the extended absorption edge to the visible region, these nanocomposites were further used as a photocatalyst to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-TiO2/Gr nanocomposite with 2% graphene exhibits enhanced photocatalytic stable hydrogen production i.e. similar to 5941 mu mol h(-1) under solar light irradiation using just 0.2 gm nanocomposite, which is much higher as compared to P25, undoped TiO2 and TiO2/Gr nanocomposite. The enhancement in the photocatalytic activity is attributed to `N' doping as well as high specific surface area and charge carrier ability of graphene. The recycling of the photocatalyst shows a good stability of the nanocomposites. This work may provide new insights to design other semiconductor deposited graphene novel nanocomposites as a visible light active photocatalyst.

Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors

Graphene-MnO2 composite supercapacitor material accomplished tactically using liquid-liquid and solid-liquid interface reaction techniques - Patil, Sagar H.; Gaikwad, Aarti P.; Waghmode, Babasaheb J.; Sathaye, Shivaram D.; Patil, Kashinath R. (New Journal of Chemistry, 2020)
A novel methodology is described to grow architectures of 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite materials to be used in supercapacitors. The in situ growth of the three-dimensional MnO2 fiber-network over the surface of graphene layers is achieved at the solid-liquid interface. The composite electrode shows good electron and charge transfer, rapid plus reversible faradaic reactions and excellent cyclic ability in electrochemical studies. The electrochemical properties of the as-prepared GNS-MnO2/FTO electrode material were assessed by cyclic voltammetry and galvanostatic charge/discharge tests. The specific capacitance of GNS-MnO2 reaches 683 F g(-1) at a current density of 2.2 A g(-1) and shows excellent cycle stability, retaining 96.9% of its initial capacitance up to 5000 cycles. A coulomb efficiency of about 99% displayed by the GNS-MnO2/FTO electrode is an excellent performance for a desired supercapacitor material. Herein, the charge storage mechanism in 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite is discussed in detail. Furthermore, at an elevated current density of similar to 10.86 A g(-1), a power density of similar to 6.235 kW kg(-1) is achieved, maintaining an energy density of similar to 7.99 kW h kg(-1); thus, it demonstrates promising potential as an electrode material for supercapacitor application.